CFD analysis of thermal-hydraluic behaviors in a LBE cooled 19-pin wire wrapped bundle under porous lumped blockage conditions. (February 2021) - Lyu, Kefeng; Ma, Xudan; Wang, Haitao; Chen, Chong; Fei, Guangsheng
Highlights: RANS CFD were performed on oxide porous lumped blockage in HLM cooled bundle. Factors such as blockage size,  its location, porosity and so on were investigated. Flow and temperature fields of fluid and solid around the blockage were obtained. Abstract: Flow blockage in fuel assemblies is a severe accident that must be considered in reactor design and safety analysis. Porous type internal blockages are more likely to occur within fuel assemblies by the accumulation of suspended impurities following coolant flow. For lead-based reactor, the deposition of oxide impurities with low thermal conductivity are expected to represent a safety concern. In this paper, three-dimensional flow and heat transfer behaviors of LBE were obtained using commercial CFD software. A parametric study including blockage geometry, its position and blockage particle properties were performed systematically. It was found that the local hotspot may occur in the wake zone downstream of blockage for plate type blockage, while for column type blockage, the hotspot occurred within the blockage zone. The peak cladding temperature could exceed the design limit (usually 500 °C for LBE system) even for a small length column blockage. But flow resistance is not strongly influenced by the axial growth of blockage. That means the column type porous blockage, which is more likely to occur in wire spacer bundle, is difficult to be detected in advance. Blockage particle properties have great impacts on the peak cladding temperature. Moreover, cladding that are partly exposed to blockage are subjected to large circumferential temperature variation (>140 °C for case 4) and may result in huge thermal stress.